PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA DAN ADVERSITY QUOTIENT - Siti Fadillah; Kms. Muhammad Amin Fauzi; Anita Yus (EJoES (Educational Journal of Elementary School), 2021)
This study aims to determine: (1) whether there is a significant effect between learning (problem based learning and conventional) on students 'mathematical representation abilities, (2) whether there is a significant effect between learning (problem based learning and conventional) on students' adversity quotient. , (3) whether there is an interaction between learning (problem based learning and conventional) and Early Mathematics Ability to students 'representational abilities, (4) is there an interaction between learning (problem based learning and conventional) and Early Mathematics Ability to students' adversity quotient. This research is a quasiexperimental research. The sample was selected by cluster random sampling consisting of two classes. The data obtained were analyzed using two-way ANOVA in the SPSS 20 program. The results showed that: 1) there was a significant effect between learning (problem based learning and conventional) on students' mathematical representation abilities, 2) there was a significant effect between learning (problem based learning and conventional) on students' adversity quotient, 3) there is an interaction between learning (problem based learning and conventional) and Early Mathematics Ability to student representation skills 4) there isn’t an interaction between learning (problem based learning and conventional) and Early Mathematics Ability to adversity quotient